Tingkat Penerapan dan Pengetahuan Wanita Tani Tentang Industri Rempeyek pada Kelompok Wanita Tani Mekar Sari di Desa Bukian Kecamatan Payangan Kabupaten Gianyar - DEWA, PAKSI BALI; SUDARTA, I WAYAN; HANDAYANI, M. TH. (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Women, as a component of society has a role and strategic function as an integral part in development process. Coaching women farmers in rural areas through a group called Kelompok Wanita Tani (KWT), which has the objective to assist agricultural activities, in improving the incomes and welfare of the family. The purpose of this study was to determine the level of knowledge and application of KWT Mekar Sari members of industrial rempeyek. The scope of this research is the study of knowledge (cognitive) and application (psychomotor) KWT Mekar Sari members of rempeyek industrial Bukian Village, Payangan District, Gianyar. This study used a qualitative descriptive analysis.Based on the survey results revealed that the level of application and level of knowledge KWT Mekar Sari members of rempeyek industrial in the Bukian village classified in good category, with the achievement of knowledge score 79% and 78,38% for application. In effort to improve the knowledge and application KWT Mekar Sari members of rempeyek industrial, it can be suggested to pay attention to the quality of rempeyek packaging by using plastic sealer and handling the waste from rempeyek is very needed as fuel cooking stove and sold in the form of a kilogram. Keywords: knowledge, application, women farmers, rempeyek industrial.